Therapeutic Interventions of Major Parasitic Foodborne Diseases - Hatoon A. Niyazi, (Journal of King Abdulaziz University: Medical Sciences, 2024)
Foodborne parasites (FBP) are commonly linked to marginalized populations, particularly in areas with poor sanitation and inadequate water supply. Animal products serve as a key route of foodborne diseases. The ingestion of contaminated water and food could lead to zoonotic diseases. Foodborne parasites are comprised of shellfish, fresh produce, and water-contaminating protozoans (Toxoplasma, Cryptosporidium, and Giardia), fishborne parasites (Anisakid nematodes), and meat-borne parasites (Trichinella). Globally, novel foodborne pathogens have emerged after the food system commercialization. Despite the recurrent antibiotic resistance, albendazole and mebendazole (MBZ) (Trichinellosis); pyrimethamine/clindamycin, pyrimethamine/ sulfadiazine, or trimethoprim/sulfamethoxazole (Toxoplasmosis); Nitazoxanide (Cryptosporidiosis); nitroimidazoles (Giardiasis); and niclosamide or praziquantel (10 mg/kg) (Diphyllobothriosis and Taeniasis) are mainly employed to counter these pathogens. Fortunately, rapid progress in this field has raised the biological understanding of parasitic infections, which could help in eliminating parasitic foodborne outbreaks. This review discusses the major FBP and related therapeutic interventions